Efficacy of Nivolumab in a Patient with Metastatic Renal Cell Carcinoma and End-Stage Renal Disease on Dialysis: Case Report and Literature Review - Jawaher Ansari; Muhammad Ali; Ashraf Farrag; Arwa M. Ali; Abdulaziz Alhamad (Case Reports in Immunology)
Treatment of patients with metastatic renal cell carcinoma (mRCC) and end-stage renal disease (ESRD) on dialysis poses a therapeutic challenge, particularly as this patient group was excluded from the pivotal clinical trials. In addition, there is uncertainty regarding drug dosing/pharmacokinetics, lack of safety and efficacy data, and potential for increased toxicity when using targeted therapy or immunotherapy for the management of patients with mRCC on dialysis. Nivolumab, an anti-programmed death-1 immune checkpoint inhibitor antibody, is indicated for the treatment of patients with mRCC who have received prior antiangiogenic therapy. Given the above-mentioned uncertainties, clinicians may be reluctant to use nivolumab for this patient population, leading to potential denial of life-prolonging medications. We report the case of a 72-year-old gentleman with mRCC and ESRD on dialysis who received second-line nivolumab therapy and achieved an excellent symptomatic and radiological response, remaining progression-free for over 22 months. In addition, we have reviewed the pharmacokinetic data and published retrospective case studies to review the management options for patients with mRCC and ESRD on dialysis.